2013
DOI: 10.1093/infdis/jit496
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Syphilis and Gonorrhea Incidences in Guangdong Province, China

Abstract: The high burden of syphilis in China presents a unique opportunity to examine temporal trends. This study used wavelet transformation and Fourier analysis to assess the presence of temporal oscillations in the incidence of syphilis among adults, gonorrhea, and congenital syphilis over 11 years in China's largest province. This study found a significant annual oscillation trend in the incidence of adult syphilis, consistent with a peak during July-September, which was 4-fold higher than the trough, which occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Specifically, the seasonal fluctuation showed that the CT incidence in Shenzhen decreased from December to February each year, with the trough in February, but later increased. The result was similar to previous studies on other sexually transmitted diseases such as gonorrhea and syphilis in China [31][32][33], which could be interpreted by what is called 'Spring Festival effects' [34]. The 'Spring Festival effects' refer to the fact that the number of new infections dropped during the Spring Festival, followed by a rise [32,34].…”
Section: Epidemiology and Infectionsupporting
confidence: 89%
“…Specifically, the seasonal fluctuation showed that the CT incidence in Shenzhen decreased from December to February each year, with the trough in February, but later increased. The result was similar to previous studies on other sexually transmitted diseases such as gonorrhea and syphilis in China [31][32][33], which could be interpreted by what is called 'Spring Festival effects' [34]. The 'Spring Festival effects' refer to the fact that the number of new infections dropped during the Spring Festival, followed by a rise [32,34].…”
Section: Epidemiology and Infectionsupporting
confidence: 89%
“…Wearing less or more revealing clothing is another reason probably related to the increase of sexual behaviors during this time [30] . In addition, increased relative risk under excessive heat conditions, which may be associated with increased testosterone levels which may cause more fidgets and sexual activities, was also expected [1] . Another potential factor that contributes to the elevated relative risk of sexually transmitted diseases during excessively hot days is that employees often receive extra bonuses such as the High Temperature Allowance and thus have more money available on these days.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, we specified the lagged effect of humidex up to 12 weeks (the minimum lag was set to 0 by default) to calculate the cumulative effect of humidex [1, 24, 25] . The degrees of freedom for ns (time) were specified within 5–10, and for both the space of the predictor and the lag dimension of weekly humidex, within 3–6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stillbirth and neonatal damage due to congenital syphilis are thought to rival the early life burden of HIV infection, though arguably syphilis receives far less attention [ 6 ]. Incidence of syphilis is rising in many countries, including the UK and China [ 7 , 8 ]. There are over 100 million new cases of gonorrhoea globally each year [ 9 ], and incidence is also increasing in England [ 5 ].…”
mentioning
confidence: 99%